Dynamic modulus, internal friction, and transient creep at high temperature in austenitic stainless steel. (March 2022) - Qu, Tongzhang; Jackson, Ian
Abstract: Dynamic shear modulus and internal friction of a coarse-grained austenitic stainless-steel sample (AISI 304) were measured by mechanical spectroscopy technique at elevated temperatures to 1200 ℃ and oscillation periods ranging from 1 s to 1000 s. The results were fitted to an extended Burgers model, showing a new thermally activated dissipation peak with relaxation strength 0.075 ± 0.005 superimposed on the high-temperature background. Across the temperature interval 1000–750 ℃, the dissipation peak traverses the 1–1000 s observational window with an activation energy of 210 ± 14 kJ/mol. Complementary time-domain information acquired by microcreep testing within the same temperature range reveals the extent to which the inelastic strain is recoverable (i.e. anelastic). A transient creep map was constructed to quantitatively analyze the contribution of different deformation mechanisms. The combined analysis involving Burgers model and a transient creep map highlights the likely role of stress-induced migration of dislocations in both the anelastic relaxation and the viscous deformation. This study thus provides a more robust understanding of the mechanical behavior of austenitic stainless steel at high temperatures and low strain amplitudes with implications, for example, for its use in jacketing other materials for mechanical testing under conditions of high temperature and pressure. Graphical Abstract: ga1